Effectiveness of ADI-STEM to Improve Student’s Science Literacy Skill - Sigit Purnomo; Yuni Sari Rahayu; Rudiana Agustini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to analyze the effectiveness of the Argument-Driven Inquiry (ADI)–Science, Technology, Engineering, and Mathematics (STEM) model in improving students' scientific literacy abilities. Method: The method used in this research is the literature review method. The literature review is a type of research used to collect data and information by collecting and reviewing various references. This study analyzes as many as 20 national and international articles that can be accounted for. The articles used were published in 2015-2022. The steps taken in this study were identifying topics, finding and selecting appropriate articles, analyzing and synthesizing the literature, and concluding. Result: Based on the results of the studies and analyses that have been carried out, it can be concluded that (1) the application of the ADI learning model can improve students' scientific literacy skills; (2) the ability to argumentation skills to increase students' scientific literacy; (3) integrating STEM into the learning process is also able to improve scientific literacy skills because STEM provides opportunities for students to identify real-life problems. Novelty: This study reveals that students' scientific literacy can be increased effectively by integrating ADI and STEM. These findings invite researchers, educators, and the government to develop learning that facilitates ADI-STEM learning.